Diagnosis and Clinico-Surgical Management of Secondary Laminitis due to Ovarian Tumour in a Kathiawari Mare - Padaliya, Nilesh. R.; Vadalia, Jignesh V; Dodia, Vaibhav V; Ravel, Rupesh J; Fefar, Dhaval T; Talekar, Shivaji H (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Granulosa cell tumours (GCTs) are the most common ovarian tumours in equine which involves around 2.5% of all tumours of horses and 85% of reproductive tract tumours (McCue et al. 2006). Tumours may originate from tissue present within the equine ovary. GCTs are most often first detected during either routine reproductive examination for breeding or when behavioral changes caused by the presence of the tumour in ovary requiring further investigation (McKinnon and Barker, 2010). Mares with GCTs remain infertile due to atrophy of the contralateral ovary, which has been variably associated with elevated serum inhibin, testosterone or anti-Mullerian hormone concentrations (Ball et al., 2012). Surgical removal is regarded as the treatment of choice for GCTs (McCue et al., 2006). Surgical removal of the affected ovary almost always results in the resumption of normal heat cycles and the ability to carry a normal pregnancy. Lameness in mare which suffered from GCT was also reported earlier by Meagher et al. (1977). Various scientists reported different technique for removal of affected ovary. Standing laparoscopic ovariectomy is associated with a lower complication rate than other surgical methods like colpotomy (Colbern and Reagan 1987), flank, paramedian or ventral midline celiotomy (Lee and Hendrickson, 2008; Azizi et al., 2014). Most of GCTs are benign and affect the left ovary (McCue et al. 2006; Korany et al., 2020). The present document reports clinical diagnosis and surgical management of secondary laminitis due to ovarian tumour in a Kathiawari mare by left flank ovariectomy of the affected ovary.
Keywords: Kathiawari Mare; Laminitis; Ovarian tumour; Surgical intervention.